The Song of Songs: Interpreted by Early Christian and Medieval Commentators - Egan, Keith J. (Cistercian studies quarterly, 2005)
Reviews the book "The Song of Songs: Interpreted by Early Christian and Medieval Commentators," translated and edited by Richard A. Norris.